Evaluation of DNA Binding, Cleavage, and Cytotoxic Activity of Cu(II), Co(II), and Ni(II) Schiff Base Complexes of 1-Phenylindoline-2,3-dione with Isonicotinohydrazide - Ramadoss Gomathi; Andy Ramu; Athiappan Murugan (Bioinorganic Chemistry and Applications)
One new series of Cu(II), Co(II), and Ni(II) Schiff base complexes was prepared through the condensation reaction between 1-phenylindoline-2,3-dione with isonicotinohydrazide followed by metalation, respectively. The Schiff base ligand(L), (E)-N′-(2-oxo-1-phenylindolin-3-lidene)isonicotinohydrazide, and its complexes were found soluble in DMF and DMSO solvents and characterized by using the modern analytical and spectral techniques such as elemental analysis, conductivity, magnetic moments, IR, NMR, UV-visible, Mass, CV, and EPR. The elemental analysis data of ligand and their complexes were well agreed with their calculated values in which metal and ligand stoichiometry ratio 1 : 2 was noted. Molar conductance values indicated that all the complexes were found to be nonelectrolytes. All the complexes showed octahedral geometry around the central metal ions. Herein, we better characterized DNA binding with the complexes by UV-visible and CD spectroscopy and cyclic voltammetry techniques. The DNA cleavage experiments were carried out by Agarose gel electrophoresis method and the cytotoxicity experiments by MTT assay method. Based on the DNA binding, cleavage, and cytotoxicity studies, Cu and Ni complexes were found to be good anticancer agents against AGS-human gastric cancer cell line.